Dose-dependent efficacy and safety of drugs in patients with chronic heart failure? - Lysenko, V. A.; Syvolap, V. V.; Лисенко, Владислав Андрійович; Сиволап, Віталій Вікторович (My University, 2021)
Treatment of chronicheart failure(CHF) is very controversial. The question of optimal doses of beta-blockers, ACE inhibitors, aldosterone receptor antagonists, statins in patients with CHF hadn’t been definitively resolved. Achieving the maximum tolerated doses of drugs, although associated with reduced mortality, but is accompanied by an increase in side effects of drugs.
Keywords: Chronic heart failure; ACE inhibitors; MRAs; diuretics; statins; reatment